On-farm evaluation of drip irrigation system on coffee production in Western Oromia, Ethiopia - Genemo, Gudeta; Bedane, Habtamu; Mekonen, Eshetu (International Journal of Agricultural Research, Innovation and Technology, 2023)
Ethiopian coffee production is greatly hampered by frequent droughts.This study aimed to evaluate the performance of a drip irrigation system for coffee production on a farm. Additionally, it estimated the amount of water required for coffee crops. An experiment was conducted on a 5-year-old coffee plant with 2m spacing between lines and 2m between plants. Catch cans were used to evaluate the system performance of the installed drip irrigation system. Based on these, the average hydraulic characteristics of the installed drip irrigation system, distribution uniformity was 93.55%, Christiansen uniformity coefficient was 95.40%, flow variation was 18.52%, and coefficient of variation was 5.59%. Coffee plants grew and produced more when irrigation was used. A fresh cherry yield of 6785 kg ha-1 was obtained under irrigated coffee and 2346 kg ha-1 under non-irrigated coffee. Compared to non-irrigated coffee, irrigated coffee had the highest crop water use efficiency of 2.5 kg ha-1 mm-1, and the lowest was obtained 1.7 kg ha-1 mm-1, under non-irrigated coffee. Similarly, irrigated coffee had the highest irrigation water use efficiency (3.6 kg m-3), whereas non-irrigated coffee had the lowest (1.4 kg m-3). These findings show that drip irrigation, compared to non-irrigated coffee plants, enhances yield and water use efficiency by 65% and 60%, respectively. In order to boost production, yield, yield components, and irrigation water use efficiency, drip irrigation is a helpful irrigation technique in locations with limited water resources and extended drought spells. Int. J. Agril. Res. Innov. Tech. 13(1): 42-47, June 2023